Religion in Right-Wing Ecological Discourse. A Critical Content Analysis of a Far Right Periodical - Gärtner, Claudia (Journal of empirical theology, 2025)
While the climate crisis was denied for many years in right-wing movements, shifts in discourse have become apparent recently. Right-wing populists and extremists are developing their own narratives, such as population growth in the Global South. Religious references also become relevant in these right-wing narratives but empirical studies on religion in right-wing environmental discourse have been rare for the German-speaking region so far. The paper examines religious motifs and arguments in the new-right periodical Die Kehre representing the line of thought of the new-right discourse on ecology. 15 issues of the journal are analysed with the help of the structuring qualitative content analysis. The analysis aims to develop a first descriptive assessment of the significance of religion in the right-wing ecological discourse. Therefore, this paper is also critical to the thesis that religion contributes substantially to global climate justice.